Pokolenie Z w przestrzeni edukacji formalnej: potrzeby i wyzwania - Blachowska-Szmigiel, Marzena (Studia Edukacyjne, 2023)
The article addresses the role and tasks of the modern school and university in relation to the educational needs of Generation Z, born and raised in the realities of liquid modernity. Given the peculiarity of these realities, the key need of contemporary society in general, and of Generation Z in particular, appears to be the development of learning competences. The role and task of the school and university therefore boils down to teaching how to learn, to enjoy discovering the truth and sharing it. The aim of this article is to answer the questions to what extent school and university institutions fulfil this role and task, and what challenges they face.